Association between arteriovenous access flow and ventricular function: A cross-sectional study - Rachmat Ageng Prastowo, Rachmat
Abstract Background: Permanent hemodialysis access comes with a myriad of problems on top of the well-known benefits; flow disturbances, risk of infection and revision being among them. All of these could eventually lead to impaired cardiac function. Even so, the relationship between impaired cardiac function due to arteriovenous access in patients undergoing hemodialysis has not been clearly described. This study aimed to analyze the relationship of flow in an artificial arteriovenous access with left and right ventricular function in patients with chronic kidney disease (CKD) undergoing hemodialysis at a referral hospital in Indonesia.